2022
DOI: 10.3390/agriculture12030318
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach to Predict Air Temperature and Relative Humidity inside Mechanically and Naturally Ventilated Duck Houses: Application of Recurrent Neural Network

Abstract: The duck industry ranks sixth as one of the fastest-growing major industries for livestock production in South Korea. However, there are few studies quantitatively predicting the internal thermal and moisture environment of duck houses. In this study, high-accuracy recurrent neural network (RNN) models were used to predict the internal air temperature and relative humidity of mechanically and naturally ventilated duck houses. The models were developed according to the type of duck houses, seasons, and environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…(6) Promoting comprehensive rural development By combining the duck industry with rural tourism, ecological agriculture, and other projects, the diversified development of the rural economy can be promoted, and the sustainability of the projects can be further enhanced by encouraging the community to participate in the management and operation of the breeding projects (Lee et al, 2022;Karunathilake et al, 2023). This comprehensive development strategy can create new economic growth fields in rural areas, promote cooperation and exchange between community members, jointly promote the prosperity of duck industry and related industries, and provide an effective way to realize the comprehensive development of the rural economy and society.…”
Section: ) Strengthen Policy and Financial Supportmentioning
confidence: 99%
“…(6) Promoting comprehensive rural development By combining the duck industry with rural tourism, ecological agriculture, and other projects, the diversified development of the rural economy can be promoted, and the sustainability of the projects can be further enhanced by encouraging the community to participate in the management and operation of the breeding projects (Lee et al, 2022;Karunathilake et al, 2023). This comprehensive development strategy can create new economic growth fields in rural areas, promote cooperation and exchange between community members, jointly promote the prosperity of duck industry and related industries, and provide an effective way to realize the comprehensive development of the rural economy and society.…”
Section: ) Strengthen Policy and Financial Supportmentioning
confidence: 99%
“…Research conducted by Arora et al, said the prediction results of the air quality index for various cities showed that the RNN produced higher accuracy with the smallest MAPE of 4,70% [6]. Another study was conducted by Lee and friends, that the RNN algorithm can accurately predict air temperature and relative humidity within 1% error [7]. Besides that.…”
Section: Introductionmentioning
confidence: 95%
“…Zhang et al made multiple attempts to apply artificial neural network models ( 43 ), single-feature LSTM model ( 44 ), and multifeature LSTM model ( 45 ) to forecast VOC concentrations emitted from furniture, classroom, and actual residence, with acceptable outcomes. Deep learning models, including RNN and LSTM models, have gained recognition for their efficacy in predicting indoor pollutant concentrations, and are also playing an important role in controlling the internal environment of smart farming facilities ( 46 , 47 ). As an inseparable component of human living environment, the in-cabin environment has also captured great attention recently.…”
Section: Introductionmentioning
confidence: 99%